Exploring the Interaction Mechanism between Persimmon Proanthocyanidins and Mucin Based on Fluorescence Spectroscopy - Zhenzhen GE; Yuxiang ZHAO; Qiaoqiao HU; Zelong LIU; Rongzu NIE; Wei ZONG; Siqun JING (Shipin gongye ke-ji)
To determine the influence of mucin on the intestinal digestion and release of proanthocyanidins derived from persimmon, the physicochemical characteristics of persimmon proanthocyanidins-mucin complexes and the interaction mechanisms between persimmon proanthocyanidins and mucin were analyzed using laser particle size analyzer, differential scanning calorimetry, Fourier-transform infrared spectroscopy, and fluorescence spectroscopy. Results indicated that the particle size and absolute ζ-potential of the complexes were positively correlated with the concentrations of persimmon proanthocyanidins and their structural units (epicatechin gallate and epigallocatechin gallate). The introduction of phenolic hydroxyl groups from persimmon proanthocyanidins decreased the thermal stability and surface hydrophobicity of mucin with an increase in persimmon proanthocyanidins concentration. Infrared spectroscopy revealed that hydrogen bonding and free amino groups participated in the reaction between mucin and persimmon proanthocyanidins. It was also found that persimmon proanthocyanidins and their structural units effectively quenched the intrinsic fluorescence of mucin, with static quenching being the dominant mechanism. Thermodynamic parameter values obtained using the Van’t Hoff equation were ∆G<0, ∆H<0, ∆S<0, demonstrating that the binding of persimmon proanthocyanidins and their structural units with mucin was a spontaneous reaction with a decrease in Gibbs free energy and was primarily driven by hydrogen bonding and van der Waals forces. In summary, the addition of persimmon proanthocyanidins and their structural units induced changes in the mucin structure and strong interactions that were primarily attributed to hydrogen bonding and van der Waals forces. The findings can serve as a reference for the design of intelligent delivery systems to enhance the bioavailability of persimmon proanthocyanidins in the intestine.